Investigation of the seminal plasma metabolome in Holstein bulls - Kostyunina Olga; Ermilov Anton; Traspov Alexey; Bakoev Faridun; Chesnokov Dmitriy; Panova Anna; Kuznetsov Alexander (BIO Web of Conferences)
The quality of semen is a key factor in selecting highly productive bulls to improve reproductive performance in livestock farming. The molecular components of spermatozoa and seminal plasma play an important role in regulating male fertility, affecting sperm motility, capacitation, cell protection, acrosome reaction, fertilization, and embryonic development. Proteins and metabolites in seminal plasma are considered potential biomarkers of reproductive status in cattle and other animal species. Metabolomics, as a method for analyzing low-molecular-weight compounds, allows for a deeper understanding of metabolic pathways and regulatory mechanisms associated with fertility. The aim of this study was to conduct a comprehensive metabolomic analysis of seminal plasma from Golsht breed bulls to identify potential fertility biomarkers. For the analysis, 79 samples of seminal plasma from Golsht breed bulls were used. Plasma was separated from spermatozoa by centrifugation, followed by metabolite extraction. The metabolomic analysis was performed using a time-of-flight mass spectrometer Sciex 6600 combined with an Agilent 1290 Infinity II liquid chromatograph. Chromatographic separation was carried out in HILIC mode, while ion detection was performed in both positive and negative ionization modes. Annotation and quantification of metabolites were done using the software packages MSDIAL and Skyline. The comprehensive metabolomic analysis identified 235 metabolites, including amino acids, nucleotides, cofactors, vitamins, and other endogenous compounds. Among the identified metabolites, key substances such as glutamic acid, glutamine, hypoxanthine, inosine, and nicotinamide were detected, which may play a significant role in regulating reproductive processes. The obtained data highlight the complexity and diversity of the metabolic profile of seminal plasma in bulls, opening new possibilities for identifying fertility biomarkers and improving selection methods for breeding animals.